Daya Terima Pempek Terhadap Berbagai Bahan Dasar Daging - Gardis Andari; Nurliah Nurliah (Musamus Journal of Agribusiness, 2020)
In general, in making pempek using sea fish, in this case, belida fish (Notopterus chitala) is ground and added with sago and other spices. Currently the consumption of pempek in South Sumatra is increasing because this food can be consumed at any time of the morning, afternoon, evening, without knowing the time so it is not difficult to get this food because it is available everywhere (street vendors and restaurants). The increasing consumption of pempek in South Sumatra has resulted in belida fish being very difficult to obtain, the effect of the difficulty of finding and obtaining belida fish has an effect on the selling price of belida fish which is very expensive in the market. There needs to be a variation in the use of pempek as a base ingredient. Therefore, this research was conducted. The method used in this study is by means of experimentation by conducting direct experiments on the use of different basic ingredients to the quality of pempek on texture, color, taste, aroma. The parameters used in this study were the organoleptic level test which gave a value of 1-5 for quality (shape, color, aroma, texture, and taste acceptability) which was carried out by 25 untrained panelists by giving a questionnaire containing the organoleptic test format ( cascade test). The organoleptic test results show that the pempek color that the panelists like is from the snakehead fish pempek, the pempek aroma that the panelists like the most is the aroma of the chicken pempek because it is not fishy, ​​the pempek taste that panlenis likes is chicken pempek, the highest value of acceptance or preference is found in chicken pempek. Keywords: chicken, snakehead fish, catfish